Esophageal stress softening recovery is altered in STZ-induced diabetic rats. (19th July 2019) - Jiang, Hongbo; Zhao, Jingbo; Liao, Donghua; Wang, Guixue; Gregersen, Hans
Abstract: This study investigated stress softening recovery in intact, separated muscle and mucosa-submucosa esophageal tubes in streptozotocin-induced diabetic rats. Fifteen Wistar rats were made diabetic (DM group) by intraperitoneal injection of 50 mg kg −1 streptozotocin and another 11 rats served as Sham group by injection of saline. All rats survived for 8-weeks. Three series of inflation-deflation loadings at luminal pressure levels of 0.5, 1.0 and 2.0 kPa were carried out on different esophageal tubes. Five distension cycles on each pressure level were done in Ca ++ -free Krebs solution before and after KCl activation in Ca ++ -containing Krebs solution. The wall stiffness and stored energy recovery were compared between two groups. The stiffness was biggest in the DM group for the intact tube at pressure 0.5 kPa (P < 0.01) and for the muscle tube at all pressure levels (P < 0.05). Energy recovery induced by stress softening and stiffness loss recovery were significantly smaller in the DM group than in the Sham group for the intact esophagus and separated tubes at all pressure levels (P < 0.05, P < 0.01). In conclusion, the reversible stress softening and passive stiffness recovery were altered in STZ-induced diabetic rats. This study fills a gap in the knowledge about diabetes-induced esophageal remodeling.